Transformaciones del paisaje y modos de vida: una perspectiva geohistórica en Dalcahue, Chiloé, Chile - Henríquez Olmedo, Valentina (2024)
This article explores the transformations of the landscape in Dalcahue, Chiloe, and how these transformations are influenced by changes in the lifestyles or livelihoods of the people of Chiloe, from the 1960 earthquake to the end of the 2010s. A qualitative methodology is applied, through the analysis of interviews with older adults who have managed to live through the time period of the case study: witnessing the abandonment and geographical isolation of the archipelago in the 1960s (and earlier), the irruption of aquaculture activities, and as a consequence, urban expansion and the abandonment of rural activities. The article concludes that the changes in the landscape are due to changes in the lifestyles of Chiloe society, as well as to external agents of globalization, such as the arrival of the salmon and fish farming industries.